Making Callaloo in Detroit - Hernandez, Lolita (Book collections on Project MUSE., 2014)
Drawing on memories of growing up in Detroit with Caribbean roots, Hernandez reveals a hidden community that craves sun and saltwater, dances to calypso, and makes callaloo, bakes, buljol, sanchocho, and pelau in their kitchens. Making Callaloo in Detroit explores questions of how we assimilate and retain identity, how families evolve as generations pass, how memory guides the present, and how the spirit world stays close to the living.--Publisher's description.